(untitled) (Agricultural Engineering, 2016)
The paper presents methodology of measuring the values which characterize the thermal balance in a horticultural facility. Thermal transmittance through a plastic tunnel cover and the ratio of solar radiation energy conversion into heat were analysed in detail. The research was carried out in real time with closed ventilators, where no plants were cultivated during the tests. The utility surface area was 144 m2, the cover was 289 m2 and its volume was 508 m3. Basing on the standard relations, first of all, thermal transmittance through a cover was measured. The ratio was measured with the use of standard criteria equations. Then, a correlation equation, which makes its course dependent on the climate parameters (the wind speed and temperature difference between the interior of the facility and its surroundings), was found. Knowing the course of the ratio in the function of the climate parameters, the value of the ratio of solar radiation conversion into heat stored in the facility was measured. Both parameters (thermal transmittance and solar radiation conversion ratios) were calculated from the thermal balance equaition where the change of the energy stored inside the facility was compared to the heat losses through a cover (for thenual transmittance) and the profit (in case of solar radiation conversion). For the obtained values, using the non-linear estimation procedure (with quasi-Newtom method with maintenance of the correlation coefficient of 0.001) the change of both ratios in the function of easily measured parameters of climate inside and outside the facility was found out. In the investigated conditions, the average value of thermal transmittance through a cover was 5.32W∙m-2 ∙K-1, and the solar radiation conversion into heat was 0.36. The values and their course from the climate parameters inside and outside the facility may be used for controlling the amount of supplied heat and location of ventilators.